Alain Badious Paulus-læsning - Karlsen, Mads Peter (Dansk Teologisk Tidsskrift, 2010)
In philosophical and theological circles there has been a tendency to read Alain Badiou’s book Saint Paul – La fondation de l’universalisme as part of a more widespread ‘return to religion’ in the field of philosophy. This article argues that if we read Badiou’s book in this context we risk a serious misunderstanding of the relationship between philosophy and religion and religion and politics in Badiou’s work. The argument proceeds in two stages. Firstly, by examining Badiou’s ‘formalistic’ approach to Paul, a more general view of the relation between philosophy and religion is uncovered in his work. Secondly, the subsequent discussion aims to illustrate how we can understand Badiou’s claim in Saint Paul that his intention in the book ‘is neither historicizing nor exegetical, but subjective through and through’. This ‘subjective intention’ is illuminated through a survey of three more or less coherent issues in Badiou’s book, summarized under the following headings: Badiou’s Paul as a ‘literary instantiation’, a ‘philosophical intervention’ and a ‘political inspiration’. At the heart of all three issues is the same concern, namely a concern for a specific conception of truth, which Badiou believes can be found in Paul.